2021
DOI: 10.1101/2021.01.26.427765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rapid evolution of flagellar ion-selectivity in experimental populations ofE. coli

Abstract: Motility provides a selective advantage to many bacterial species and is often achieved by rotation of flagella that propel the cell towards more favourable conditions. In most species, the rotation of the flagellum, driven by the Bacterial Flagellar Motor (BFM), is powered by H+ or Na+ ion transit through the torque-generating stator subunit of the motor complex. The ionic requirements for motility appear to have adapted to environmental changes throughout history but the molecular basis of this adaptation, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Different triple mutations of residues at the periplasmic side of MotB TM switched the dual-functional stator unit into either a proton-driven or sodium-driven one, indicating that ion specificity is located along the channel at the region preceding the critically conserved aspartate [65]. Introduction of sodium-driven PomAB into E. coli through CRISPR/ Cas-mediated genome engineering showed that, when sodium is lacking, PomAB can spontaneously mutate, which allows it to use the proton gradient as driving force [66]. Thus, additional studies are needed to fully understand the molecular basis underlying the ion selectivity mechanism of the stator unit.…”
Section: Open Accessmentioning
confidence: 99%
“…Different triple mutations of residues at the periplasmic side of MotB TM switched the dual-functional stator unit into either a proton-driven or sodium-driven one, indicating that ion specificity is located along the channel at the region preceding the critically conserved aspartate [65]. Introduction of sodium-driven PomAB into E. coli through CRISPR/ Cas-mediated genome engineering showed that, when sodium is lacking, PomAB can spontaneously mutate, which allows it to use the proton gradient as driving force [66]. Thus, additional studies are needed to fully understand the molecular basis underlying the ion selectivity mechanism of the stator unit.…”
Section: Open Accessmentioning
confidence: 99%
“…We evaluated the ionic power source (H + or Na + ) of our functional MotA-ASRs in low Na + condition (~1 mM) using a minimal swim plate without tryptone or yeast extract and where NaCl had been substituted with KCl (Islam et al, 2020; Ridone et al, 2021). Here, we checked whether the tested strains could generate swim rings or not in the low sodium environment.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this this version posted October 18, 2022. ; https://doi.org/10.1101/2022.10.17.512626 doi: bioRxiv preprint (Ridone et al, 2022) may mean that there may be many combinations of A and B subunits which are able to power rotation and many combinations which cannot. It is therefore suitable to resurrect MotBs that co-existed with MotAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations